Rapid Temporal Control of Foxp3 Protein Degradation by Sirtuin-1 - van Loosdregt, Jorg; Brunen, Diede; Fleskens, Veerle; Pals, Cornelieke E. G. M.; Lam, Eric W. F.; Coffer, Paul J. (PLOS ONE, 2011)
Maintenance of Foxp3 protein expression in regulatory T cells (Treg) is crucial for a balanced immune response. We have previously demonstrated that Foxp3 protein stability can be regulated through acetylation, however the specific mechanisms underlying this observation remain unclear. Here we demonstrate that SIRT1 a member of the lysine deacetylase Sirtuin (SIRT) family, but not the related SIRTs 2–7, co-localize with Foxp3 in the nucleus. Ectopic expression of SIRT1, but not SIRTs 2–7 results in decreased Foxp3 acetylation, while conversely inhibition of endogenous SIRT activity increased Foxp3 acetylation. We show that SIRT1 inhibition decreases Foxp3 poly-ubiquitination, thereby increasing Foxp3 protein levels. Co-transfection of SIRT1 with Foxp3 results in increased Foxp3 proteasomal degradation, while SIRT inhibition increases FOXP3 transcriptional activity in human Treg. Taken together, these data support a central role for SIRT1 in the regulation of Foxp3 protein levels and thereby in regulation of Treg suppressive capacity. Pharmacological modulation of SIRT1 activity in Treg may therefore provide a novel therapeutic strategy for controlling immune responses.